Pengaruh Amoniasi Mahkota Buah Nenas (Ananas comosus Merr) Terhadap Kecernaan (In Sacco) Neutral Detergent Fiber (NDF) dan Acid Detergent Fiber (ADF) - Pangaribuan, Rotua; Nasution, Ahmad (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The  experiment was conducted in order to know the effect of ammoniated phineapple crown on the in sacco digestibility of neutral detergent fiber (NDF) and acid detergent fiber (ADF). Material used were phineapple crown, urea as a source of ammonia for ammoniation process and one 3 – year male Madura  cattle  for  in  sacco  digestibility  application.  The  experiment  was  arranged  to  a  completely randomized design with 4 treatments and 4 replications. T0 was untreated phineapple crown, T1 was amonia treated phineaplle crown with 3 % urea, T2 was  treated phineaplle crown with 6 % urea and T3 was treated phineaplle crown with 9 % urea. Result of experiment showed that ammoniation process did affect NDF and ADF digestibilities, but there was no significant effect of the urea level  for NDF and ADF digestibilities.